Atypical presentation of sickle cell disease - Aziz, Md. Abdul; Sarkar, Surozit Kumar; Rahman, Farzana; Biswas, Showrab; Baqi, Saqi Md. Abdul; Begum, Masuda (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
A 20 year old female presented with a history of frequent syncopal attack since her childhood. Each episode persisted 5-10 min without having any aggravating factor or prodrome. She had persistent generalized bodyache aggravating during the winter. She had jaundice and episodic abdominal pain. She received 1 unit of blood transfusion 4 months back and improved sympto-matically. Patient was mildly anemic, moderately icteric and had mild splenomegaly. Over these long periods of her illness she was thoroughly evaluated several times. Her biochemical and neurological evaluation revealed no abnormalities. But she was treated with anticonvulsant for long time empirically without significant improvement. Her CBC showed microcytic hypochromic anemia. She was negative for Wilsons disease. Reticulocyte count was high. Coombs test was negative. Osmotic fragility test was positive. Hemoglobin electrophoresis revealed Hb-S 60%. Sickling test was found positive. Finally it was diagnosed as a case of HbS/?+.